Identification of Tumor Suppressor Genes via Cell Fusion and Chromosomal Transfer - Lung, Hong Lok; Cheung, Arthur Kwok Leung; Ko, Josephine Mun Yee; Cheng, Yue; Lung, Maria Li (IntechOpen, 2012)
None